Mathematical Analysis of Blood Flow Through Stenosed Arteries With body Acceleration. - Sankar, D S (2010)
The mathematical analysis discusses the pulsatile flow of blood through stenosed narrow artery with Body acceleration,treating blood as Herschel-Bulkley fluid.